Fuzzy Inference System Pada Produksi Bibit Ikan Nila Menggunakan Algoritma Tsukamoto - Juan Panjaitan; Johannes Fernando (LPPM STIKOM Tunas Bangsa, 2020)
This study aims to apply the Tsukamoto fuzzy algorithm to predict the production of tilapia seedlings in breeders must increase effective production in accordance with customer demand. The variables used to predict tilapia seedlings are demand, supply, production. The data source of this research was obtained by interview and direct observation to the production site of tilapia fish that is located in Pulo Siborna district. Panei, kab. Simalungun. It is hoped that this research can help tilapia seed breeders in producing tilapia seedlings, especially for tilapia seed breeders.